2016
DOI: 10.1371/journal.pone.0161231
|View full text |Cite|
|
Sign up to set email alerts
|

Virus-Like Nanoparticle Vaccine Confers Protection against Toxoplasma gondii

Abstract: The inner membrane complex (IMC) of Toxoplasma gondii as a peripheral membrane system has unique and critical roles in parasite replication, motility and invasion. Disruption of IMC sub-compartment protein produces a severe defect in T. gondii endodyogeny, the form of internal cell budding. In this study, we generated T. gondii virus-like particle particles (VLPs) containing proteins derived from IMC, and investigated their efficacy as a vaccine in mice. VLP vaccination induced Toxoplasma gondii-specific total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 26 publications
0
53
0
Order By: Relevance
“…All animal experiments were performed following the institutional animal care and use institutional animal care and use committee (IACUC) guidelines (permit number: KHUASP (SE)-18-050). T. gondii ME49 and RH strains were maintained and used for experimental infections as previously described [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…All animal experiments were performed following the institutional animal care and use institutional animal care and use committee (IACUC) guidelines (permit number: KHUASP (SE)-18-050). T. gondii ME49 and RH strains were maintained and used for experimental infections as previously described [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In spite of these efforts, vaccine incorporating the aforementioned strategies failed to provide sufficient protection in mice. Contrastingly, our previous works have demonstrated that virus‐like particles (VLPs) vaccines expressing various T gondii proteins could provide adequate protection against T gondii ME49 in murine models 9‐11 . However, reduced inflammatory responses in the brain induced by VLPs immunization upon T gondii ME49 infection has not been investigated in any of the previous works.…”
Section: Introductionmentioning
confidence: 90%
“…VLP vaccines can stimulate powerful humoral and cellular immune responses, representing one of the most appealing approaches for a vaccine platform by mimicking the main structural and functional characteristics of viruses [ 101 102 ]. Moreover, they can be produced in insect cell expression systems, where foreign antigens can be displayed [ 102 ]. It has been reported that VLPs are being useful and safe as vaccine candidates that could provide stronger and longer-lasting protection against toxoplasmosis [ 98 ].…”
Section: Vaccines Based On Live-attenuated Vectorsmentioning
confidence: 99%